Sensitive-Video Analysis - Moreira, Daniel; Goldenstein, Siome; Rocha, Anderson (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2017: Anais do XXX Concurso de Teses e DissertaçõesDO - 10.5753/ctd.2017.3466, 2017)
Sensitive videos that may be inadequate to some audiences (e.g., pornography and violence, towards underages) are constantly being shared over the Internet. Employing humans for filtering them is daunting. The huge amount of data and the tediousness of the task ask for computer-aided sensitive videoanalysis, which we tackle in two ways. In the first one (sensitive-video classification), we explore efficient methods to decide whether or not a video contains sensitive material. In the second one (sensitive-content localization), we explore manners to find the moments a video starts and ceases to display sensitive content. Hypotheses are stated and validated, leading to contributions (papers, dataset, and patents) in the fields of Digital Forensics and Computer Vision.